A new approach for professional dental bleaching using a polymeric catalyst primer - Dias, Marlon Ferreira [UNESP]; Martins, Beatriz Voss [UNESP]; de Oliveira Ribeiro, Rafael Antonio [UNESP]; Leite, Maria Luísa [UNESP]; Ortecho-Zuta, Uxua [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (Wiley, 2023)
Objective: Evaluate the influence of a polymeric catalyst primer (PCP) on esthetic efficacy (EE), degradation kinetics of hydrogen peroxide (H2O2), and trans-amelodentinal cytotoxicity (TC) of bleaching gels. Materials and Methods: The following groups were established: G1: No treatment (NC, negative control); G2: PCP; G3: 10% H2O2; G4: PCP + 10% H2O2; G5: 20% H2O2; G6: PCP + 20% H2O2; G7: 35% H2O2 (positive control); G8: PCP + 35% H2O2. To determine EE, enamel/dentin discs (E/DDs) were stained and subjected or not to bleaching protocols for 45 min. To assess TC, the E/DDs were adapted to artificial pulp chambers. The extracts (culture medium + gel components diffused through E/DDs) were applied to odontoblast-like MDPC-23 cells. The viability (VB), oxidative stress (OxS), morphology (SEM), amount of H2O2 diffused and the production of hydroxyl radical (OH•) were assessed (two-way ANOVA/Tukey/paired Student t-test; p < 0.05). Results: The highest EE was found in G8 (p < 0.05), and G4, G6, and G7 did not differ statistically (p > 0.05). In G4, the limited H2O2 diffusion reduced OxS and increased cell VB (p < 0.05). Conclusions: Coating the enamel with PCP containing 10 mg/ml of manganese oxide before applying the 10% H2O2 bleaching gel maintains the EE of conventional in-office bleaching and minimizes the toxic effects of this esthetic therapy. Clinical Significance: Coating the enamel with a PCP before applying the bleaching gel may potentiate the EE of the conventional in-office tooth bleaching and reduce the toxicity of this professional therapy to the dental pulp.
Keywords: color science; dental materials; odontoblasts; tooth bleaching; toxicity